Antibiogram Study of Bacteria Isolated from Subclinical Mastitis in Dairy Cattle of Kirtipur and Chandragiri Municipalities, Kathmandu, Nepal - Paudel, M.; Bohara, B.; Prasai, T.; Bhattarai, S.; Gompo, T.R. (International Journal of Applied Sciences and Biotechnology, 2023)
The dairy sector in Nepal has a high potential for growth, but unfortunately, its progress is impeded by diseases such as mastitis. The purpose of the current investigation was to identify the predominant bacterial species in mastitis-affected cattle milk and to ascertain the most efficacious antibacterial treatment against the bacterial isolates. The study was conducted from 17th August 2022 to 12th February 2023 in lactating cattle of the Kirtipur municipality and Chandragiri municipality of Kathmandu district, Nepal. A total of 640 milk samples from 160 cattle were collected randomly from cattle farms of Kirtipur and Chandragiri municipality of Kathmandu district. Initial screening for mastitis was conducted on collection sites by the California Mastitis Test (CMT) and further bacterial isolation and identification were carried out at the Central Veterinary Laboratory using standard bacterial techniques and the antibiogram were evaluated based on CLSI guidelines. Among 640 samples collected from 160 cattle, 3.91% (25/640) tested CMT-positive at the individual quarter level, whereas the prevalence at the cow level was 15.62% (25/160). The major bacterial species isolated, in subsequent culture of CMT positive samples, were Staphylococcus spp. (10, 40%), E. coli (6, 24%), Streptococcus spp. (5, 20%), Enterococcus spp. (2, 8%), Bacillus spp. (1, 4%), and Klebsiella spp. (1, 4%).. Antibiogram study reveals that major gram-positive bacteria, Staphylococcus spp., Streptococcus spp., Enterococcus spp., and Bacillus spp. were highly sensitive to Ampicillin, Florfenicol, and Gentamicin while the major gram-negative bacteria, E. coli, and Klebsiella spp. were highly sensitive to Florfenicol, Gentamicin, Trimethoprim/Sulfamethoxazole and Ceftriaxone. Hence, early diagnosis and careful monitoring of antimicrobial susceptibility before therapeutic intervention are essential to prevent high economic losses due to mastitis and to mitigate the potential risk of antimicrobial resistance in the livestock population.